One-step (18)F labeling of biomolecules using organotrifluoroborates - Liu, Zhibo (Nat Protoc, 2015)
Herein we present a general protocol for the functionalization of biomolecules with an organotrifluoroborate moiety so that they can be radiolabeled with aqueous (18)F fluoride ((18)F(−)) and used for positron emission tomography (PET) imaging. Among the β(+)-emitting radionuclides, fluorine-18 ((18)F) is the isotope of choice for PET, and it is produced, on-demand, in many hospitals worldwide. Organotrifluoroborates can be (18)F-labeled in one step in aqueous conditions via (18)F–(19)F isotope exchange. This protocol features a recently designed ammoniomethyltrifluoroborate, and it describes the following: (i) a synthetic strategy that affords modular synthesis of radiolabeling precursors via a copper-catalyzed ‘click’ reaction; and (ii) a one-step (18)F-labeling method that obviates the need for HPLC purification. Within 30 min, (18)F-labeled PET imaging probes, such as peptides, can be synthesized in good chemical and radiochemical purity (>98%), satisfactory radiochemical yield of 20–35% (n > 20, non-decay corrected) and high specific activity of 40–111 GBq/µmol (1.1–3.0 Ci/µmol). The entire procedure, including the precursor preparation and (18)F radiolabeling, takes 7–10 d.